PHENOMENON OF CREATIVE ACTIVITY IN COPYRIGHT - Білоусов, Віталій Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the concept and features of creative activity as a prerequisite of the copyright object creation are researched in the article. The absence of such research and the scientific definition of creative activity actually makes controversial and unjustified judgments and arguments of scholars and practitioners. Not finding out what such creativity and creative activity is, it is impossible to raise the issue of protecting rights to the results of intellectual activity. The solution of problems specific to creative work, is concentrated in special legal norms - the norms of copyright and patent law. Since these norms are calculated not on any, but only on creative activity, it is necessary to establish what such creativity is and what it differs from other types of socially useful work. Methods of research: the motives of creative activity are analyzed, the components of the creative process are determined. The numerous doctrinal definitions of creativity and creative activity are given, the causes of productive creative work are associated with the development of the human brain, which, using analysis and synthesis, observing nature, induced man to create not only new means of production, but also new means of knowledge, while satisfying this spiritual needs. Results: in the copyright law of creative activity is given a decisive importance, which causes the emergence of exclusive rights to works of science, literature and art. It is established that the basis of creativity is the growth of the material and spiritual needs of man, in connection with which there is an intuitive appearance of new artistic images. However, not every act of human creation is seen as an act of creativity. By its nature, creative work is productive. The difference between it and reproductive labor is that the first creates a new one, while the second one is new only in quantitative terms and only reproduces the earlier created. Creativity is nothing but a conscious productive act, the distinguishing feature of which is its qualitative novelty. Discussion: discussion issues on the definition of creative activity, its components, stages, results and causes of productive creative work.